2011
DOI: 10.1515/hf.2011.010
|View full text |Cite
|
Sign up to set email alerts
|

Near infrared spectroscopy (NIRS) as a potential tool for monitoring trade of similar woods: Discrimination of true mahogany, cedar, andiroba, and curupixá

Abstract: Mahogany is one of the most valuable woods and was widely used until it was included in Appendix II of the Convention on International Trade in Endangered Species as endangered species. Mahogany wood sometimes is traded under different names. Also, some similar woods belonging to the Meliaceae family are traded as “mahogany” or as being of a “mahogany pattern”. To investigate the feasibility of the use of near infrared spectroscopy for wood discrimination, the mahogany (Swietenia macrophylla King.), andiroba o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
70
0
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 108 publications
(78 citation statements)
references
References 25 publications
1
70
0
7
Order By: Relevance
“…As a nondestructive detection technology, near-infrared (NIR) spectroscopy coupled with discriminant analysis is an effective tool with several uses: to discriminate blue-stained wood (Via et al 2008), to classify the type of fungal decay in wood (Fackler et al 2007;Yang et al 2008), to identify the type of preservatives in wood (So et al 2004), and to identify the wood species (Schimleck et al 1996;Tsuchikawa et al 2003;Pastore et al 2011). In many discriminant analysis methods, partial least squares discriminant analysis (PLS-DA) and soft independent modeling of class analogy (SIMCA) have been the most common methods used to analyze the data of NIR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…As a nondestructive detection technology, near-infrared (NIR) spectroscopy coupled with discriminant analysis is an effective tool with several uses: to discriminate blue-stained wood (Via et al 2008), to classify the type of fungal decay in wood (Fackler et al 2007;Yang et al 2008), to identify the type of preservatives in wood (So et al 2004), and to identify the wood species (Schimleck et al 1996;Tsuchikawa et al 2003;Pastore et al 2011). In many discriminant analysis methods, partial least squares discriminant analysis (PLS-DA) and soft independent modeling of class analogy (SIMCA) have been the most common methods used to analyze the data of NIR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…NIRS-based methods have been developed to measure a wide range of wood characteristics (Tsuchikawa 2007). It has been used to estimate extent of decay (Fackler et al 2007, Stirling et al 2007) and durability (Flaete andHaartveit 2004, Gierlinger et al 2004), and to differentiate wood species (Tsuchikawa et al 2003, Pastore et al 2011 and treated wood waste (Feldhoff et al 1998, So et al 2004. Models have been developed to measure linseed oil uptake (Eriksson et al 2011), retention of borate and coppercontaining preservatives (So et al 2007, Taylor andLloyd 2007), and to differentiate untreated wood and wood treated with CBP formulations containing 3-iodo-2-propynyl butylcarbamate (IPBC)/cypermethrin, IPBC/propiconazole, and permethrin, propiconazole, and tebuconazole (Zahri et al 2008).…”
Section: Rod Stirlingmentioning
confidence: 99%
“…Antti et al [10] determined that a PLS model could be used to distinguish individual species from mixed wood chips including Swedish pine, Swedish spruce, and Polish pine. Pastore et al [11] discriminated true mahogany from similar species using PLS-DA, Horikawa et al [12] used NIR spectroscopy in combination with multivariate analysis to distinguish between P. densiflora and P. thunbergii, and Hwang et al [13] also reported that the identification of P. densiflora and P. densiflora for. erecta could be possible using chemometric approaches.…”
Section: Introductionmentioning
confidence: 99%